The UEFA European Football Championship 2012 and pop nationalism in Poland: between confirmation and contestation. Issue 5 (2nd September 2016) - Jaskulowski, Krzysztof; Majewski, Piotr
Abstract : Poland and Ukraine jointly hosted the European Football Championship in 2012. The Polish media and government portrayed Euro 2012 as the culmination of the post-communist transformation that started in 1989, a great national celebration and proof that Poland belonged to the family of 'modern' nations. Drawing on ethnographic research, we look beyond the official discourse and analyse Euro 2012 'from below' in our paper. We focus on analysing the different meanings attributed to Euro 2012 in Poland in the context of the dominant discourse. Referring to Stuart Hall, we distinguish and analyse three readings of Euro 2012, namely the dominant ('celebrators'), negotiated ('indifferentists', 'modernisers') and oppositional ('radical nationalist', 'rebels') readings.